MAKNA JAMINAN TANAH DALAM PERJANJIAN KREDIT TANPA AKTA PEMBERIAN HAK TANGGUNGAN PADA LPD DESA ADAT KEPAON - Dewi, Putu Widhia Laksmi; Anom, I Gusti Ngurah (Jurnal Hukum Mahasiswa, 2024)
LPD is a financial institution owned by indigenous villages that runs a savings and loan business. Credit, of course, needs a guarantee. One of the collaterals used in granting credit is land. The use of land as collateral must be tied to APHT. In LPD Kepaon, not all loans guaranteed by land certificates are tied to APHT. The purpose of this study is to determine the function of guarantees in providing credit by LPD Desa Adat Kepaon and to determine the position of land guarantees in credit agreements without APHT at LPD Desa Adat Kepaon. The research method used by the author is empirical legal research. The results of this study show that the function The guarantee in providing credit by LPD Desa Adat Kepaon is to guarantee the repayment of debtors if the debtor defaults, with the guarantee will reduce the risk of loss for LPD, related to the position of land as collateral in a credit agreement without APHT by LPD Desa Adat Kepaon is that the object of guarantee for the land cannot be registered as an object of guarantee of dependent rights, by not being registered, the right of liability for the land never existed so that the land used as collateral in the provision of credit by the LPD of Kepaon Traditional Village was only positioned as ordinary material security which if in the future a default occurred would result in the LPD of Kepaon Traditional Village not having the right to carry out direct execution of the guarantee.